Roscovitine-treated He La cells finalize autophagy later than apoptosis by downregulating Bcl-2 - Çoker Gürkan, Ajda; Köse, Betsi; Bıçkıcı, Güven; Palavan Ünsal, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; KILBAŞ, PELİN ÖZFİLİZ (Spandidos Publ Ltd, Pob 18179, Athens, 116 10, Greece, 2015)
The cell cycle is tightly regulated by the family of cyclin-dependent kinases (CDKs). CDKs act as regulatory factors on serine and threonine residues by phosphorylating their substrates and cyclins. CDK-targeting drugs have previously demonstrated promising effects as cancer therapeutics both in vitro and in vivo. Roscovitine, a purine-derivative and specific CDK inhibitor, has been demonstrated to arrest the cell cycle and induce apoptosis in a number of different cancer cell lines, including He La cervical cancer cells. In the present study, roscovitine was able to decrease both the cell viability and cell survival as well as induce apoptosis in a dose-dependent manner in He La cells by moiulating the mitochondrial membrane potential. The decrease of anti-apoptotic B-cell lymphoma 2 (Bcl-2) and Bcl-2 extra large protein expression was accompanied by the increase in pro-apoptotic Bcl-2-associated X protein and P53-upregulated modulator of apoptosis expression. The marked decrease in Bcl-2 following exposure to roscovitine (20 mu M) for 48 h prompted us to determine the autophagic regulation. The outcome revealed that roscovitine triggered Beclin-1 downregulation and microtubule-associated light chain 3 cleavage starting from 12 h of incubation. Another biomarker of autophagy, p62, a crucial protein for autophagic vacuole formation, was diminished following 48 h. In addition, monodansyl cadaverin staining of autophagosomes also confirmed the autophagic regulation by roscovitine treatment. The expression levels of different Bcl-2 family members determined whether apoptosis or autophagy were induced following incubation with roscovitine for different time periods. Downregulation of pro-apoptotic Bcl-2 family members indicated induction of apoptosis, while the downregulation of anti-apoptotic Bcl-2 family members rapidly induced autophagosome formation in HeLa cells.
Keywords: Roscovitine; Cervical cancer; Autophagy; Apoptosis; Bcl-2; Breast-cancer cells; R-Roscovitine; Beclin 1; Seliciclib CYC202; Carcinoma-cells; Cervical-cancer; X-L; Protein; Phosphorylation; Therapy